Absence of Floating Ribs with Corresponding Thoracic Vertebrae of Black Bengal Goat (Capra hircus) - Shil, Subrata Kumar; Ahad, Abdul; Parvez, Md. Anwar; Al Noman, Md. Abdullah; Quasem, Md. Abul (Indian Journal of Veterinary Anatomy, 2013)
A black Bengal goat (Capra hircus) revealed 12 pairs of ribs and 12 thoracic vertebrae instead of typical 13 pairs. In this condition, basal lobe of the lung extended up to the base of the 10th rib. The spleen was located below the proximal part of the 12th rib to middle of 8th rib of left side obliquely. The caudate lobe of liver was out of the caudal border of last rib. The left kidney was located below the transverse processes of first and second lumbar vertebrae whereas, right was under the second, third and fourth lumbar vertebrae. These abnormalities did not accompany with any other skeletal deformities.